DEIKSIS PERSONA DALAM BAHASA INDONESIA - Pranawa, Erry (MAGISTRA, 2004)
This research is intended to describe the forms of the pronoun. Observation method is used in collecting the data. The analysis uses substitution and expansion techniques. The result of this study shows that substitution technique proves that pronoun aku, saya, kamu, and engkau are acceptable if positioned ad subject or object, and function as agent and patient. Mean while, prnoun daku and dikau are acceptable if positioned as object, and fuction as patients. Substitution technique proves that pronoun elements show as backward constituens if fonem /d/ is not the first fonem in a word, and pronoun element as constituents take the forward position if fonem /d/ is the first fonem in the word. Expansion technique proves that dia, but not ia, can take the backward position if fuctions as explaining features. For a possessive construction, pronoun element which does not have /d/ as the first fonem of a word is a grammatical ulterance if taking the backward position.